Variação espacial da dieta de larvas de Auchenipterus osteomystax (Silurifome; Auchenipteridae) e ingestão de microplástico em tributários no Alto rio Paraná - Silva, Diego Rangel da (2021)
Feeding in the early stages of fish life is considered to be the most crucial for their survival, a period in which the larvae undergo abrupt changes and are highly vulnerable to fluctuations of food available in the environment. This study aimed to evaluate the diet of Auchenipterus osteomystax larvae and to investigate the ingestion of microplastic in three tributaries (Aguapeí, Verde and Pardo) of the Engenheiro Sergio Motta Hydroelectric reservoir, known as Porto Primavera, Alto Rio Paraná. Sampling occurred monthly in the reproductive period (October to March) between the years 2007 to 2020. A total of 119 larvae were analyzed. The diet was composed mainly of insects with emphasis on Diptera. Significant differences were observed in the items consumed in the tributaries, as well as among the stages of larval development. The analysis of the Individual Indicator Value (IndVal) showed that larvae collected in the Aguapeí river presented as the most relevant food items Brachycera and Chironomidae larva, and in the Pardo river, the items that contributed most were vegetable detritus and Nematocera. On the other hand, for the Verde River, there was no highlight for any item consumed by the larvae. During larval development, in the pre-flexion (PF) stage there was a predominance of insect remains Aquatic, followed by vegetable detritus, however IndVal did not indicate any relevant items in the diet. The flexion (FL) and post-flexion (FP) larvae consumed mainly insect remains aquatic and adult Diptera, respectively. Flexion larvae (FL) had Brachycera as the most relevant item, while post flexion larvae (FP) had insect remains, Chironomidae larva, Hemiptera, Ephemeroptera, adult dipterans, Nematocera and Cerapotogonidae pupae. Microplastics (blue and colorless, soft and rigid filaments) were ingested mainly by pre-flexed larvae and with a high incidence in those sampled in the Verde and Pardo rivers, possibly associated with the proximity of the sampling sites to the urban areas and more intense fishing activities. Based on the assumptions of the results, it instigates us to develop more studies in these areas, with the same theme, involving other species.